2019
DOI: 10.1002/adsc.201801590
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Methyl Ether Cleavage: Characterization of the Corrinoid‐Dependent Methyl Transfer System from Desulfitobacterium hafniense

Abstract: The ether functionality represents a very common motif in organic chemistry and especially the methyl ether is commonly found in natural products. Its formation and cleavage can be achieved via countless chemical procedures. Nevertheless, since in particular the cleavage often involves harsh reaction conditions, milder alternatives are highly demanded. Very recently, we have reported on a biocatalytic shuttle catalysis concept for reversible cleavage and formation of phenolic O-methyl ethers employing a corrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…This type of substrate was not accepted by the previously described MTase from D. hafniense . 31 , 34 36 However, when MT-vdmB was used in combination with the carrier protein vdmA from the same organism as described in literature, only very low conversion for demethylation of veratrol 1a (10 mM substrate concentration) was observed (3%) when using a 5-fold molar excess of 3,4-dihydroxybenzaldehyde 4c as a methyl acceptor ( Scheme 1 ). The acceptor was converted to the regioisomers vanillin 2c and isovanillin 3c in a 3:1 ratio.…”
Section: Results and Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This type of substrate was not accepted by the previously described MTase from D. hafniense . 31 , 34 36 However, when MT-vdmB was used in combination with the carrier protein vdmA from the same organism as described in literature, only very low conversion for demethylation of veratrol 1a (10 mM substrate concentration) was observed (3%) when using a 5-fold molar excess of 3,4-dihydroxybenzaldehyde 4c as a methyl acceptor ( Scheme 1 ). The acceptor was converted to the regioisomers vanillin 2c and isovanillin 3c in a 3:1 ratio.…”
Section: Results and Discussionmentioning
confidence: 86%
“… 32 , 33 A specific methyltransferase dhaf4610 from Desulfitobacterium hafniense ( D. hafniense ) has been recently employed for the methylation of catechols and demethylation of guaiacol derivatives. 34 36 Unlike the well-investigated S -adenosyl methionine (SAM)-dependent methyltransferases, 37 39 which are restricted toward methylation only, this MTase 29 , 40 has been shown to enable both methylation and demethylation in a reversible manner. 34 , 35 Thereby, the MTase transfers the methyl group from the cofactor methylcobalamin (Me-Cob III ) 41 44 to the substrate giving cobalt in the oxidation state I (Cob I ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of holo ‐CP. The functional holo ‐CP was obtained by reconstitution of the corrinoid protein with exogenous cofactor (methyl cobalamin) under inert atmosphere as already described [16b] . For this purpose, methyl cobalamin (2 mM) was dissolved in the presence of betaine (3 M) and DTT (2 mM) in TRIS/HCl buffer (50 mM, pH 7, 0.5 mM DTT, 0.1 mM PMSF) to form a reconstitution buffer.…”
Section: Methodsmentioning
confidence: 99%
“…[13] Previously, we showed that these cobalamin methyltransferases (cob-MT) are able to shuttle the methyl group between structurally related molecules, thus from guaiacol derivatives to catechol derivatives. However, that reaction was limited by its equilibrium (Scheme 1 A); [14] By omitting a methyl acceptor, isomerization, and thus intramolecular methyl transfer, was observed (Scheme 1 B). [15] This isomerization was also a prominent side reaction in the case of the intermolecular methyl transfer due to equilibria.…”
mentioning
confidence: 99%